Low and high-intensity water-based training equally improve disability and functional performance in women with multiple sclerosis but has no effects on IL10, IL17, and S100 protein biomarkers - Askari, Roya; Jafari, Maryam; Hosseini Kakhki, Seyed Alireza; Etemadifar, Masoud; Sadat Azarnive, Marzie; Gentil, Paulo; Khademosharie, Mitra; Shekarchizadeh, Parivash (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Purpose. Multiple sclerosis (MS) is a demyelinating neurodegenerative disease of the central nervous system that involves a wide range of symptoms including loss of physical function. This study investigated the effects of eight weeks of water exercise training with two different intensities on Interleukin 10 (IL10), Interleukin 17 (IL17), and low molecular-weight calcium-binding proteins (S100), disability, and functional performance in women with MS.Methods. Forty-five relapsing-remitting women with MS and an Expanded Disability Status Scale (EDSS) score 3.5 were randomly divided into three groups: water-based low-intensity aerobic training (LIT), water-based high-intensity aerobic training (HIT), and a control group (CON). After eight weeks of water-based exercises, blood samples were collected 24 hours before the first session and 48 hours after the last training session. Physical performance was evaluated using a 30-second sit-to-stand test, the total number of elbow flexions performed with 2.5 kg dumbbells, 2-minute walking distances, and a timed up-and-go test (TUG).Results. There were no significant differences within or between groups in IL10, IL17, and S100 indices (p > 0.05). A significant difference was observed in the disability and functional indices after eight weeks, with higher values for the LIT and HIT groups compared to the CON group (p < 0.01), with no difference between them.Conclusions. Eight weeks of water-based exercises improve functional disability in patients with MS despite no changes in inflammatory biomarkers.
Keywords: aerobic training; aerobic exercise; resistance training; rehabilitation; neurodegenerative disease; muscle strength